Non-thermal plasma for acne treatment and aesthetic skin improvement - Chanchai Chutsirimongkol (2018)
© 2014 by Begell House, Inc. Non-thermal plasma/cold atmospheric plasma (NTP/CAP) technology, which can generate low-temperature plasma in normal atmosphere, has been recognized widely as a new emerging tool with potential applications in life science and biomedical fields. During the last 10 years, many reports have published regarding NTP, confirming its safety and efficacy in health care and various medical applications. The promising future of NTP technology has aroused our interest to study a novel NTP device in detail. The device generates dielectric barrier discharge (DBD) with direct contact or noncontact at a few-millimeter gap between electrode surface and skin. NTP is generated by ionizing the surrounding air on the electrode surface, discharging directly to the targeted tissue. We have conducted clinical trials of this device called the “BIOPLASMA Cell Modulator” (developed by Photo Bio Care, Thailand) as a new application for acne and aesthetic skin improvement.